FROM THE SURREAL TO REAL: FRANZ KAFKA’S PILGRIMAGE TO HUMAN CONSCIENCE - Sekhar, P, Raja; Manjusha, Ch.V (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Franz Kafka, often shrouded in existentialism and interpreted through lenses of Jewish pessimism, remains one of the most enigmatic figures in modern literature. Despite the brevity of his literary corpus, Kafka’s works challenge the most astute readers and literary critics, weaving profound truths about the human condition into seemingly dissuasive narratives. His simplicity, paradoxically, masks essential truths that resonate deeply with the complexities of life, often dismissed by frustrated critics as purposeless. Yet, at the heart of Kafka’s writing lies a profound commitment to humanism, articulated through every word and idea. This article delves into Kafka’s seminal works, personal diaries, and the critical perspectives they have inspired, offering a fresh exploration of his principles of precise conscience and their enduring relevance in understanding the human truth.